Novel extremophilic proteases from Pseudomonas aeruginosa M211 and their application in the hydrolysis of dried distiller's grain with solubles - Flores-Fernández C.N. (2019)
Proteases are the most important group of industrial enzymes and they can be used in several fields including biorefineries for the valorization of industrial byproducts. In this study, we purified and characterized novel extremophilic proteases produced by a Pseudomonas aeruginosa strain isolated from Mauritia flexuosa palm swamps soil samples in Peruvian Amazon. In addition, we tested their ability to hydrolyze distillers dried grains with solubles (DDGS) protein. Three alkaline and thermophilic serine proteases named EI, EII, and EIII with molecular weight of 35, 40, and 55 kDa, respectively, were purified. EI and EIII were strongly inhibited by EDTA and Pefabloc being classified as serine-metalloproteases, while EII was completely inhibited only by Pefabloc being classified as a serine protease. In addition, EI and EII exhibited highest enzymatic activity at pH 8, while EIII at pH 11 maintaining almost 100% of it at pH 12. All the enzymes demonstrated optimum activity at 60°C. Enzymatic activity of EI was strongly stimulated in presence of Mn2+ (6.9-fold), EII was stimulated by Mn2+ (3.7-fold), while EIII was slightly stimulated by Zn2+, Ca2+, and Mg2+. DDGS protein hydrolysis using purified Pseudomonas aeruginosa M211 proteases demonstrated that, based on glycine released, EIII presented the highest proteolytic activity toward DDGS. This enzyme enabled the release 63% of the total glycine content in wheat DDGS protein, 2.2-fold higher that when using the commercial Pronase®. Overall, our results indicate that this novel extremopreoteases have a great potential to be applied in DDGS hydrolysis.